Smoke Simulation with Detail Enhancement in Ship Fires - Rui Tao; Hongxiang Ren; Xiao Yang; Delong Wang; Jian Sun (Journal of Marine Science and Engineering)
Smoke simulation is a crucial yet challenging aspect of constructing ship fire scenarios. For the Eulerian smoke simulation method, the low-resolution grid results in a loss of smoke detail, while the high-resolution grid faces significant computational costs. To address this issue, a detail enhancement approach is proposed for smoke simulation in ship fire scenarios based on vortex particles, aiming at high-realism smoke simulation on a low-resolution grid. The simulation domain is first discretized using a low-resolution grid to compute the basic flow. Next, the vortex particles are sampled within the grid, and the loss of vorticity is measured before and after vortex stretching to compensate for the missing smoke details. In our approach, a geometric method is employed to efficiently capture the stretching of vortex structures. The computational results demonstrate that turbulence details can be effectively captured in a low-resolution grid while maintaining the real-time performance of the simulation. The practical application value of our approach is demonstrated in improving the realism of ship fire scenarios.